Urdu mei Quran aur Hadith k Mahawaraat - Dr. Ghulam Mustafa Khan (Islamabad Idara Tehqiqat-e-Islami, 1980)
A compilation of Mahawrat from Quran and Hadith in Urdu translation.
Keywords: Quran & Hadith